The Influence of Competency, Independency, and Professionalism on Audit Quality: (Empirical Study in Accounting Firms in Central Java) - Dewi Kartika; Bambang Agus Pramuka (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2019)
The purpose of this research is to examine the influence of competency, independency, and professionalism on audit quality. Competency, independency, and professionalism are three characteristics of a competent auditor. The population of this research is the auditor of accounting firms in Central Java. The samples of this research are employees of auditors working at accounting firm (KAP) Budiman, Wawan, Pamudji Tegal, KAP Wartono & Fellow Surakarta, KAP Sophian Wongsaro Semarang, KAP Heliantono & Semarang Branch. Forty-five questionnaires are employed in this study. Before the hypotheses testing, validity and reliability tests are run to determine the validity and reliability of the data. Hypothesis testing techniques uses regression analysis. These research results show that competency, independency, professionalism influence the quality of the audit. However, these results have to be cautiously interpreted since only few auditors’ questionnaires were worth analyzing. Future studies may increase the number of KAPs from other districts in Indonesia or using not only auditors from accounting firms but also government auditors or internal auditors.